Sender paid and authenticated messaging (SPAM) - Evan Yonathan Aryohutomo Murdiwanto. (2009)
Sender Paid and Authenticated Messaging (SPAM) is a complete framework of e-mail, sms, and chat messaging that incorporates new approach in fighting bulky unwanted message, also known as spam. Spam can exist due to the simplicity and near to no cost of sending mass e-mail. With the imposed payment economies in the system, spammers will likely be reduced and in the end defecated by the SPAM system. SPAM adopts a micropayment approach as it is desirable to have a single mechanism to handle spam effectively without high expenses on server resources. This approach is implemented by incurring a cost to the sender via a reusable token. This token is in a way similar to the stamp on snail mail, where it is a method of payment to enable the message to be sent. SPAM system consisted of various components that support each other to make a complete framework, with web-based user interface on top of it.